Drivers to Equity Valuation: Perpetuities or Annuities Approach? An Application to the main European Stock Markets (Journal of Business, Universidad del Pacífico (Lima, Peru), 2020)
Academics and practitioners have been applying equity valuation methods mainly based on discount cash flow models, residual income models or dividend discount models combined with balance sheet and income statement multiples of market comparables to analyse share price and to provide price targets for investors or even base for transactions such as mergers and acquisitions (M&A). Most of those methods rely on mathematical deductions of growing or constant perpetuities or near perpetuities (such as annuities) to attain market values. However, it is of the outmost relevance for valuation to verify how the theoretical models relate with real values and what is its relationship with companies’ firm past age. Beyond stating a non-linear relationship for valuation models and ascertain important valuation drivers, using a sample of more than 3400 European companies with cross section data, this paper contributes to the improvement of valuation model’s effectiveness by inducing non-explicit period valuation modifications to long term annuities and perpetuities considering class age intervals. This paper’s originality is supported by the study of the relation of past company age with predicted annuities, the proof of non-compliance of perpetuity-based valuation models and the contribution with new value drivers for valuation purposes.